Implementasi Kebijakan Kementerian Agama pada Masa Pandemi COVID-19 dalam Aktivitas Penyuluh Agama di Kantor Urusan Agama (KUA) Kecamatan Sukasari Kota Bandung - Nadya Zulfa Imaniar; Rodliyah Khuzai; Asep Ahmad Siddiq (Bandung Conference Series: Islamic Broadcast Communication, 2022)
Abstract. The emergence of Covid-19 made the Ministry of Religion should make a policy for religious instructors to continue their counseling assisted by virtual media, but in fact, these activities had an obstacles, including religious instructors at KUA Sukasari District where the programs had to be changed, they were required to be creative, and limited activities due to some areas being required to temporarily close. The purpose of this research is to find out the programs, communication processes, obstacles, and solutions for religious instructors at the KUA of Sukasari District during the Covid-19 pandemic. The type of research is qualitative research with descriptive analysis method with a da'wah communication theory and the data collection techniques in the form of interviews, observations, and documentation. Data analysis techniques that will be used are data reduction, data presentation, and verification. The results of this research are the program that carried out by religious instructors at the KUA of Sukasari District there is communication through virtual media and face-to-face with strict health protocols, the obstacles experienced are limitations in mastering the virtual media, building public trust, conditioning gadgets, internet and quotas disruptions, the delays in activity time, and the solution is to have an adaptive attitude and connect with the community. Abstrak. Munculnya Covid-19 membuat Kementerian Agama harus membuat sebuah kebijakan kepada penyuluh agama untuk tetap melakukan penyuluhannya yang dibantu dengan media virtual, namun nyatanya kegiatan tersebut justru mengalami hambatan, termasuk penyuluh agama di KUA Kecamatan Sukasari dimana program yang telah direncanakan harus diubah, mereka diharuskan untuk kreatif, dan kegiatan yang sangat terbatas akibat beberapa wilayah diharuskan untuk tutup sementara. Tujuan penelitian ini adalah untuk mengetahui program, proses komunikasi, hambatan, serta solusi penyuluh agama di KUA Kecamatan Sukasari pada masa pandemi Covid-19. Jenis penelitian ini yaitu penelitian kualitatif metode deskriptif analisis dengan pendekatan teori komunikasi dakwah dan teknik pengumpulan data berupa wawancara, observasi, dan dokumentasi. Teknik analisis data yang akan digunakan adalah reduksi data, penyajian data, dan verifikasi. Hasil penelitian ini bahwa program penyuluh agama KUA Kecamatan Sukasari terdapat komunikasi melalui media virtual dan tatap dengan protokol kesehatan yang ketat, hambatan yang dialami adalah keterbatasan menguasai media virtual, membangun kepercayaan masyarakat, mengkondisikan gadget, gangguan internet dan kuota, keterlambatan waktu kegiatan, dan solusinya adalah dengan adanya sikap adaptif dan saling berkomunikasi dengan masyarakat.